2001
DOI: 10.1210/endo.142.7.8278
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Specific Enhancement of Agonist-Stimulated ERK-1/2 Signaling in Uterine Artery Endothelial Cells Increases Ca2+ Sensitivity of Endothelial Nitric Oxide Synthase as well as Cytosolic Phospholipase A2*

Abstract: Uterine artery endothelial cells (UAEC) from pregnant ewes (P-UAEC) demonstrate generally enhanced ability to couple growth factor and G protein-coupled receptors to the ERK-1/2 signaling pathway and stimulate NO production independently of elevated [Ca(2+)]. Herein we investigate the signaling and vasodilator responses to ATP, an agonist that also elevates [Ca(2+)](i) in both NP and P-UAEC, to determine the relative importance of Ca(2+) vs. ERK-1/2 in the activation of eNOS. We observed in both NP-UAEC and P-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 25 publications
7
31
1
Order By: Relevance
“…Figure 1 shows representative images of cells at a density of 20%-100% and recordings of 100 lM ATP-induced [Ca 2þ ] i responses in NP-UAECs and P-UAECs at these same cell densities. Of note, the initial response in the first few minutes (less than 5 min) agreed with that described previously [7]-namely, that the initial rapid [Ca 2þ ] i release peak was of similar size in NP-UAECs and P-UAECs-but repeated [Ca 2þ ] i bursts occurred for a longer time in P-UAECs than in NP-UAECs. Some additional superimposed rapid oscillations (see inset) were also seen in P-UAECs but not NP-UAECs.…”
Section: Atp Induces Cell Density-dependent and Pregnancyenhanced Sussupporting
confidence: 89%
See 2 more Smart Citations
“…Figure 1 shows representative images of cells at a density of 20%-100% and recordings of 100 lM ATP-induced [Ca 2þ ] i responses in NP-UAECs and P-UAECs at these same cell densities. Of note, the initial response in the first few minutes (less than 5 min) agreed with that described previously [7]-namely, that the initial rapid [Ca 2þ ] i release peak was of similar size in NP-UAECs and P-UAECs-but repeated [Ca 2þ ] i bursts occurred for a longer time in P-UAECs than in NP-UAECs. Some additional superimposed rapid oscillations (see inset) were also seen in P-UAECs but not NP-UAECs.…”
Section: Atp Induces Cell Density-dependent and Pregnancyenhanced Sussupporting
confidence: 89%
“…Several investigations have confirmed that UA endothelium is more capable of agonist-dependent nitric oxide (NO) and prostacyclin production during pregnancy [2,5,6]. Our own studies have further revealed that this adaptive response of UA endothelium includes profound reprogramming at the level of postreceptor cell signaling, specifically at the level of both kinase activation and Ca 2þ signaling, particularly during the sustained phase of Ca 2þ signaling [3,4,7].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Pretreatment of UAECs with DUP 753 (10 µM), PD 123319 (10 µM), or the cotreatment of both inhibitors for 20 min showed an observable decrease in ERK2 phosphorylation to a level not significantly different from control and not significantly different from AII treatment alone. In view of this ambiguous result, we wished to confirm that AII was indeed activating ERK2 via Mitogen Activated Protein Kinase-Kinase (MEK) as previously suggested Di et al 2001). Implication of a MEK-mediated ERK2 phosphorylation event following AII stimulation was achieved using the MEK1/2 inhibitor, PD 98059 (20 µM, 20-min pretreatment) that exhibited a significant decrease in ERK2 phosphorylation (Figure 9).…”
Section: Resultsmentioning
confidence: 77%
“…Our functional data concerning the second messenger signaling responses to AII raise further questions concerning the possible role of another receptor to AII. We have previously established that AII stimulates a small but significant PLC-mediated response in NP-UAECs and P-UAECs but that there is still a pregnancy-specific enhancement of AII-mediated activation of the ERK1/2 signaling pathway (Bird et al , 2003Di et al 2001). In order to gain more insight into the possible roles of AT 1 R, AT 2 R, and perhaps previously unidentified AII receptors, we chose to look more closely at the aforementioned functional responses, particularly the dose responses.…”
Section: Discussionmentioning
confidence: 99%